Two-component thermally conductive structural adhesive

A two-component thermally conductive adhesive for electric vehicle batteries addresses the challenges of achieving high thermal conductivity and strong adhesion by using a balanced formulation of epoxy resin, reactive flexible agents, and polyamines with high thermally conductive filler content, resulting in enhanced performance and structural integrity.

JP2025510103APending Publication Date: 2025-04-14DDP SPECIALTY ELECTRONICS MATERIALS US LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024556386
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-22
Filing Date
2023-03-21
Publication Date
2025-04-14

AI Technical Summary

Technical Problem

Existing thermally conductive adhesives for electric vehicle batteries face challenges in achieving high thermal conductivity and strong adhesion while maintaining a balanced epoxy:amine ratio and minimizing the use of high molecular weight polyether amines, which can adversely affect performance.

Method used

A two-component thermally conductive adhesive is developed, with a partial resin component containing epoxy resin, reactive flexible agents, reactive silanes, and thermally conductive fillers, and a partial hardener component with polyamines, catalysts, and thermally conductive fillers. The adhesive mixture is formulated to have a thermally conductive filler concentration of 65-85% by weight and a filler content ratio of 0.7-0.9, allowing for a 1:1 mixing ratio by weight.

Benefits of technology

The adhesive achieves high thermal conductivity, strong adhesion to metal surfaces, and excellent structural properties, including high elastic modulus, wrap shear strength, and T-peel strength, while maintaining a balanced chemical composition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510103000001
    Figure 2025510103000001
  • Figure 2025510103000002
    Figure 2025510103000002
  • Figure 2025510103000003
    Figure 2025510103000003
Patent Text Reader

Abstract

Provided herein is a two-component thermally conductive epoxy adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 63 / 322,281, filed March 22, 2022, which is incorporated herein by reference. [Background technology]

[0002] Currently, there is a growing trend to produce electric vehicles in order to reduce vehicle CO2 emissions. The combination of a growing automobile market and an increasing market share for electric vehicles has led to a significant increase in the number of electric vehicles.

[0003] To achieve long driving range, batteries with high energy density are required. Currently, several battery strategies with different detailed concepts are being pursued, but what all long-range battery concepts have in common is the need to manage the heat generated during battery use. Thermally conductive adhesives are used to thermally connect the battery cells or modules to the cooling unit and fix them in place. Battery cells generate heat during charging and discharging operations. To avoid reducing efficiency and to avoid overheating that could cause dangerous thermal runaway reactions, the cells need to be kept at a suitable operating temperature (preferably 25-40°C). For these reasons, active cooling is used. Typically, a cooled water-glycol mixture is pumped into channels that cool the metal bottom plate on which the battery cells / modules are located. To link the cell modules to the cooling plate, a thermally conductive adhesive is applied and bonded to the cooling plate. For cooling efficiency, a thermal conductivity of 1 W / mK or higher is required. To bond the battery modules to the cooling plate, high lap shear strength levels are required, typically above 3 MPa, more preferably above 5 MPa, and most preferably above 7 MPa.

[0004] Cooling plates and module housings are most often designed using aluminum without the additional protection of an e-coat. Aluminum is typically passivated by a treatment, e.g. Ti / Zr coating, which provides excellent corrosion protection. Certain customers also use steel as the substrate for the battery, which can be e-coated in areas prone to corrosion or left unpainted in dry areas. With such substrates, polyurethane adhesives are typically difficult to build a strong and durable bond with a good failure mode. The best adhesion to metal can typically be achieved with the application of an epoxy adhesive.

[0005] For the easiest application and best mix quality, a 1:1 mix ratio adhesive is generally preferred by end users for automated applications. This is for several reasons, including, among others: - Least susceptible to dispensing errors, - With the same size dispenser and package (drum) of 1:1 ratio adhesive, refill times for the dispenser and drum occur simultaneously, reducing downtime.

[0006] Two-component epoxy adhesives are generally prepared by combining one epoxy component with one amine component. The commonly used bisphenol A diglycidyl ether epoxy resin (DGBPA) has an epoxy equivalent of typically 170-190 g / mol epoxy, while commonly used amines, such as the commonly used 4,7,10-trioxatridecane-1,13-diamine with a molecular weight of 220 g / mol and two primary amines, have active NH equivalent weights (NHEW) as low as 55 g / mol, or even molecules such as triethylenetetramine with an NHEW of only 22 g / mol. To design a more balanced epoxy adhesive with an epoxy:NH ratio of about 1:1, typically a large amount of very long polyetheramines (often known as Jeffamines) are used. These are commercially available as diamines with molecular weights up to 2000 g / mol (NH equivalent = 500 g / mol). This allows the formulation of adhesives with 2:1 and even 1:1 mix ratios. The use of such high molecular weight polyetheramines is not entirely desirable, as they adversely affect the glass transition temperature and strength performance, especially at elevated temperatures. In addition, the superior electrical properties of epoxy adhesives are due to the specific properties of the epoxy resins in the adhesive. Therefore, the higher the epoxy resin content in the final cured matrix, the better the electrical properties. In some applications, the higher the epoxy resin content, the better the electrical properties. 14 This is important because volume resistivity in Ohm / cm is required.

[0007] Most thermally conductive adhesives require very high filler loadings, around 70% by weight when using aluminum hydroxide ATH, to achieve thermal conductivities above 1 W / mK. Adhesives are typically designed with symmetric levels of inorganic fillers in both the epoxy and amine components to ensure that the rheology of both components is comparable. Summary of the Invention [Means for solving the problem]

[0008] In a first aspect, there is provided a two-component thermally conductive adhesive comprising: (A) A portion resin component, (a1) at least one epoxy resin; (a2) at least one reactive flexibilizer; (a3) at least one reactive silane; (a4) at least one thermally conductive filler having a concentration of [a4] (wt%) based on the total weight of part A A resin component comprising: (B) a B part hardener component, (b1) at least one polyamine; (b2) at least one catalyst capable of catalyzing the reaction of an amine with an epoxy group; (b3) at least one thermally conductive filler having a concentration of [b3] (wt%) based on the total weight of part B A B part hardener component comprising Including, A two-component thermally conductive adhesive is provided, in which, in use, part A and part B are mixed together in a volume ratio of 0.8:1 to 1.2:1 to form an adhesive mixture, the concentration of the thermally conductive filler in the adhesive mixture being 65 to 85 weight percent, based on the total weight of the adhesive mixture, and the ratio of [a4]:[b3] being 0.7 to 0.9.

[0009] In a second aspect, there is provided a method for producing an adhesive, comprising the steps of: (1) preparing a part A resin component, (a1) at least one epoxy resin; (a2) at least one reactive flexibilizer; (a3) at least one reactive silane; (a4) at least one thermally conductive filler having a concentration of [a4] (wt%) based on the total weight of part A a process comprising: (2) preparing a B part hardener component, (b1) at least one polyamine; (b2) at least one catalyst capable of catalyzing the reaction of an amine with an epoxy group; (b3) at least one thermally conductive filler having a concentration of [b3] (wt%) based on the total weight of part B a process comprising: (3) mixing part A and part B in a volume ratio of 0.8:1 to 1.2:1 to form an adhesive mixture such that the concentration of the thermally conductive filler in the adhesive mixture is 65 to 85 weight percent, based on the total weight of the adhesive mixture; A method for producing an adhesive comprising: The ratio of [a4]:[b3] is 0.7 to 0.9. A method for making an adhesive is provided.

[0010] In a third aspect, there is provided a method for bonding two substrates, comprising the steps of: (1) preparing an A part resin component, (a1) at least one epoxy resin; (a2) at least one reactive flexibilizer; (a3) at least one reactive silane; (a4) at least one thermally conductive filler having a concentration of [a4] (wt%) based on the total weight of part A a process comprising: (2) preparing a B part hardener component, (b1) at least one polyamine; (b2) at least one catalyst capable of catalyzing the reaction of an amine with an epoxy group; (b3) at least one thermally conductive filler having a concentration of [b3] (wt%) based on the total weight of part B a process comprising: (3) mixing part A and part B in a volume ratio of 0.8:1 to 1.2:1 to form an adhesive mixture such that the concentration of the thermally conductive filler in the adhesive mixture is 65 to 85 weight percent, based on the total weight of the adhesive mixture; a process in which the ratio of [a4]:[b3] is 0.7 to 0.9; (4) applying the adhesive mixture to at least one substrate; (5) bringing a second substrate into adhesive contact with the adhesive mixture; and (6) Curing the adhesive mixture A method for bonding two substrates is provided, comprising: DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The inventors have surprisingly found that the epoxy component (part A) and the amine component (part B) of a two-part epoxy adhesive can be loaded with a large bias, with the difference in filler volume content between the two components exceeding 10% by weight. The filler content of part A is reduced, for example to 60-65% by weight, which allows the content of organic epoxy resin matrix in part A to be increased, while the filler loading in part B is increased, for example to 75-80%. As a result, even though the entire adhesive has a 1:1 mix ratio by weight, the ratio of organic compounds is very close to a 2:1 mix ratio. The resulting adhesive has very high strength and very good adhesion to metal surfaces.

[0012] Definitions and Abbreviations ATH: Aluminum trihydroxide PTMEG: Poly(tetramethylene oxide) glycol DGEBA: Bisphenol A diglycidyl ether polyTHF: poly(tetramethylene oxide) glycol PBD: Poly(butadiene)diol DBTL: Dibutyltin dilaurate HDI: Hexamethylene diisocyanate PTHF: Poly(tetrahydrofuran) MDI: Methylene diphenyl diisocyanate

[0013] Polymer molecular weights reported herein are reported in Daltons (Da) as number or weight average molecular weight as measured by size exclusion chromatography (SEC). Unless otherwise specified, this refers to the number average molecular weight.

[0014] Two-component adhesives consist of part A (the resin component) and part B (the hardener component). During use, parts A and B are mixed in the desired ratio and then applied to one or more substrates.

[0015] Ingredient A Component A is (a1) at least one epoxy resin; (a2) at least one reactive flexibilizer; (a3) at least one reactive silane; (a4) at least one thermally conductive filler having a concentration of [a4] (wt%) based on the total weight of part A Includes.

[0016] Each component will be described in turn.

[0017] At least one epoxy resin (a1) Part A of the two-component adhesive comprises at least one epoxy resin. Epoxy resins useful in the adhesive composition include a variety of curable epoxy compounds and combinations thereof. Useful epoxy resins include liquids, solids, and mixtures thereof, with liquids being useful. Typically, the epoxy compounds are epoxy resins, also referred to as monoepoxides or polyepoxides. The polyepoxides useful herein can be monomers (e.g., diglycidyl ether of bisphenol A, diglycidyl ether of bisphenol F, diglycidyl ether of tetrabromobisphenol A, novolac-based epoxy resins, and trifunctional epoxy resins), higher molecular weight resins (e.g., diglycidyl ether of bisphenol A chain-extended with bisphenol A), or unsaturated monoepoxides polymerized into homopolymers or copolymers (e.g., glycidyl acrylate, glycidyl methacrylate, allyl glycidyl ether, etc.). Most desirably, the epoxy compounds contain an average of at least one pendant or terminal 1,2-epoxy group (i.e., vicinal epoxy group) per molecule. The solid epoxy resins that can be used can include bisphenol A or preferably can be based primarily on bisphenol A. Some epoxy resins include, for example, DER330, DER331, and DER671, all of which are commercially available from The Dow Chemical Company. The monoepoxides useful herein can be reactive diluents with only one 1,2-epoxy group, such as para-tert-butylphenyl glycidyl ether (Araldite DY-T), glycidyl ethers of long chain aliphatic alcohols, such as the monoglycidyl ether of a mixture of C12 and C14 alcohols (Araldite DY-E), or those with more 1,2-epoxy groups, such as the reaction product of epichlorohydrin and polypropylene glycol (DER732).

[0018] One preferred epoxy resin has the general formula:

[0019] [ka]

[0020] (wherein n ranges from 0 to about 25). has.

[0021] Exemplary epoxy resins have an epoxy equivalent weight in the range of about 170 to 195 g / mole.

[0022] Combinations of epoxy resins can be used to tailor the properties of the epoxy adhesive. In the compositions and methods, the epoxy adhesive can include any amount of epoxy resin. Preferably, the liquid and / or solid epoxy resin comprises 20% or more by weight of the epoxy adhesive, more preferably about 25% or more, 30% or more, or 35% or more by weight. Preferably, the liquid and / or solid epoxy resin comprises 65% or less by weight of the epoxy adhesive, more preferably 55% or less, or 45% or less by weight. Other amounts are shown in the examples. Ranges formed from pairs of these values ​​are also disclosed, such as 25-35% by weight, 25-65% by weight, 30-38% by weight (Adhesive AA).

[0023] When a combination of liquid and solid epoxy resins is used, any ratio can be used and can be determined by one skilled in the art. To obtain a suitable viscosity, it is usually useful to have a weight ratio of liquid epoxy resin to solid epoxy resin greater than 50:50. The epoxy adhesive composition can include liquid and solid epoxy resins in a ratio of 55:45 or more, 65:35 or more, or 70:30 or more. The epoxy adhesive composition can include liquid and solid epoxy resins in a ratio of 100:0 or less, 99:1 or less, 90:10 or less, or 85:10 or less. Other ratios are shown in the examples. Ranges formed from these pairs of values ​​(e.g., 50:50 to 100:0, 65:35 to 82:18 (adhesive AU)) are also disclosed.

[0024] Preferred epoxy resins include the following: Epoxy Liquid reaction products of epichlorohydrin and bisphenol A, e.g. DER331, having an epoxide equivalent weight (measured according to ASTM D-1652) of 1.182-192 g / eq, an epoxide percentage (measured according to ASTM D-1652) of 22.4-23.6%, an epoxide group content (measured according to ASTM D-1652) of 5200-5500 mmol / kg, and a viscosity at 25°C (measured according to ASTM D-445) of 4000-14000 mPas; Epoxy A solid epoxy resin which is a low molecular weight solid reaction product of epichlorohydrin and bisphenol A, e.g. DER671, having an epoxide equivalent weight (measured according to ASTM D-1652) of 2.475-550 g / eq, an epoxide percentage (measured according to ASTM D-1652) of 7.8-9.1%, an epoxide group content (measured according to ASTM D-1652) of 1820-2110 mmol / kg, and a melt viscosity at 150°C (measured according to ASTM D-4287) of 400-950 mPas; Particularly preferred is Epoxy 1.

[0025] The epoxy resin may be present in the adhesive at 20 to 40% by weight, more preferably 25 to 35% by weight, and especially preferably 26 to 34% by weight, based on the total weight of Part A of the adhesive.

[0026] In one embodiment, the epoxy resin is Epoxy 1 and is used at 26-29 wt %, based on the total weight of Part A of the adhesive.

[0027] In one embodiment, the A portion has an epoxy equivalent weight per liter of 1.50 to 4.50 mmol / l, more preferably 2.50 to 3.5 mmol / l, and especially preferably 3.00 to 3.30 mmol / l.

[0028] Reactive flexibilizers (a2) Part A of the two-component adhesive comprises at least one reactive flexibilizer.

[0029] Reactive flexibilizers (sometimes called tougheners) are elastomeric molecules that have end groups that are capable of reacting with an epoxy resin or an epoxy resin hardener in the presence of a catalyst, or that can be cleaved to expose end groups that are capable of reacting with an epoxy resin or an epoxy resin hardener in the presence of a catalyst.

[0030] Preferred flexibilizers for use in the compositions of the present invention are reactive polyurethane tougheners prepared by reacting at least one polyol and optional poly(butadiene) diol with a polyisocyanate in the presence of a polyurethane catalyst, optionally followed by chain extension with a diphenol and endcapping with a phenol, oxime, or molecule of formula I:

[0031] [ka]

[0032] (In the formula, R 1 and R 2 is independently selected from hydrogen and C1-C6 alkyl, n is an integer from 1 to 2, and R 3 is C1-C6 alkyl).

[0033] In another preferred embodiment, the end group or capping group is a phenol, particularly preferably a diphenol or a monophenol, particularly preferably O,O'-diallylbisphenol A or cardanol.

[0034] When the terminal group is a molecule of formula I, preferably R 1 and R 2 are independently selected from H and C1-C4 alkyl, more preferably H and C1-C2 alkyl, and particularly preferably R 1 and R 2 is H.

[0035] In a preferred embodiment, R 3 is C1 to C4 alkyl, more preferably C1 to C2 alkyl.

[0036] In a preferred embodiment, n is 1.

[0037] In another preferred embodiment, R 1 and R 2 is H and R 3 is ethyl or methyl, in particular ethyl, and n is 1. In a particularly preferred embodiment, the capping molecule is CPEE.

[0038] The at least one polyol is preferably a diol or triol, or a mixture of both. Diols are particularly preferred. In a preferred embodiment, the at least one polyol is a poly(alkylene oxide) diol. Preferred poly(alkylene oxide) diols are selected from poly(C2-C6 alkylene oxide) diols, in particular poly(tetramethylene oxide) diol ("PTMEG"), poly(trimethylene oxide) diol ("PO3G"), and mixtures thereof. The poly(alkylene oxide) diols preferably have a molecular weight in the range of 1,000 to 2,500 Da, more preferably 1,000 to 2,000 Da. PTMEG is particularly preferred. Preferably, PTMEG has a molecular weight in the range of 1,000 to 2,500 Da, more preferably 1,000 to 2,000 Da.

[0039] In a preferred embodiment, the PBD is included in the toughening agent backbone.

[0040] In another preferred embodiment, chain extension is carried out with diphenols.

[0041] In another preferred embodiment, a PBD is included and chain extended with a diphenol.

[0042] In another preferred embodiment, no PBD is included.

[0043] In another preferred embodiment, no chain extension is performed.

[0044] In another preferred embodiment, no PBD is included and no chain extension is performed.

[0045] If used, the PBD preferably has a molecular weight in the range of 1,000 to 3,500 Da, more preferably 2,800 Da.

[0046] The polyisocyanate is not particularly limited. It may be aromatic or aliphatic. Examples of suitable polyisocyanates include toluene diisocyanate, 1,6-hexamethylene diisocyanate ("HMDI" or "HDI"), methylene diphenyl diisocyanate ("MDI"), 2,2,4-trimethylhexamethylene diisocyanate (TMDI), and isophorone diisocyanate (IPDI). HMDI is particularly preferred.

[0047] The polyurethane catalyst is not particularly limited. Dibutyltin dilaurate ("DBTL") and metal carboxylates, such as bismuth carboxylate and / or zinc carboxylate, are particularly preferred. The catalyst is preferably used at 0.01 to 0.5 wt %, more preferably 0.1 wt %, based on the total weight of the toughening agent. In a preferred embodiment, the catalyst is a mixture of bismuth and zinc salts of carboxylates, and is used at 0.1 wt %, based on the total weight of the toughening agent composition.

[0048] Optional chain extension is carried out using a diphenol. O,O'-diallyl bisphenol A ("ODBA") is particularly preferred. The diphenol is preferably used in an amount of 2 to 10% by weight, more preferably 5 to 8% by weight, and especially preferred 7% by weight, based on the total weight of the toughening agent. Alternatively, the chain extender can be used in a molar ratio to the polyol of 0:1 to 1:1, more preferably 0:1 to 0.8:1, and especially preferred 0.6:1 to 0.8:1.

[0049] Reaction of the diol, polyisocyanate, and diphenol chain extender (if used) terminates the pre-capping molecule with NCO groups, followed by end-capping with a phenol, diphenol, or molecule of formula I. When a molecule of formula I is used as the end-capping group, a catalyst is used, such as at least one metal carboxylate, especially carboxylates of zinc and / or bismuth.

[0050] The toughening agent preferably comprises 40-90% by weight, more preferably 45-85% by weight, more preferably 50-85% by weight of a polyol, in particular a poly(alkylene oxide) diol, based on the total weight of the toughening agent. Particularly preferably, the toughening agent comprises 40-90% by weight, more preferably 45-85% by weight, more particularly preferably 50-85% by weight of PTMEG, based on the total weight of the toughening agent.

[0051] When present, the PBD is preferably present in the toughening agent at 10 to 25 wt %, more preferably 12 to 18 wt % PBD, based on the total weight of the toughening agent, with PBD having a molecular weight of 2,800 Da being especially preferred.

[0052] In a preferred embodiment, the toughening agent comprises toluene diisocyanate as the polyisocyanate, poly(propylene oxide) diol as the polyol, and cardanol as the end-capping group.

[0053] In another preferred embodiment, the toughening agent comprises hexamethylene diisocyanate as the polyisocyanate, poly(tetramethylene oxide) diol as the polyol, and O,O'-diallyl bisphenol A as the chain extender and end-capping group.

[0054] A preferred method for producing the toughening agent is the following process: 1. First reaction step: A polyol, preferably a poly(alkylene oxide) diol (more preferably PTMEG) and PBD (if used) are heated to 120-130°C. The mixture is heated under vacuum for 25-35 minutes. The mixture is cooled to 50-70°C. When the temperature reaches 50-70°C, a diisocyanate (preferably HDI) is added and the mixture is mixed for 2-5 minutes. A polyurethane catalyst (e.g. an organotin compound) is then added and the mixture is reacted under a neutral atmosphere (e.g. nitrogen or argon) at 75-90°C (bath temperature) for 40-50 minutes. 2. Second reaction stage: The chain extender (if used) is added and the mixture is stirred under a neutral atmosphere (e.g. nitrogen or argon) at 85-95°C (bath temperature) for 50-70 minutes. Third reaction step (when a molecule of formula I is used as the end group): An end-capping molecule of formula I (e.g., CPEE) is added and the mixture is stirred for 80-95 minutes at 85-95°C (bath temperature) under a neutral atmosphere (e.g., nitrogen or argon). The mixture is stirred for 10 minutes at 95°C under vacuum for degassing. Third reaction step (when diphenols or monophenols are used as end groups): Add monophenols or diphenols and stir the mixture at 85-95°C (bath temperature) for 80-95 minutes under a neutral atmosphere (e.g. nitrogen or argon). Stir the mixture at 95°C for 10 minutes under vacuum for degassing.

[0055] The reactive flexibilizer is preferably present in the A part at 2 to 10% by weight, more preferably 3 to 8% by weight, and especially preferably 4 to 6% by weight, based on the total weight of the A part.

[0056] In a preferred embodiment, the reactive flexibilizer is a polyurethane-based flexibilizer and is present at 2-10% by weight, more preferably 3-8% by weight, and especially preferably 4-6% by weight, based on the total weight of part A.

[0057] In another preferred embodiment, the reactive flexibilizer is prepared by reacting at least one polyol and optional poly(butadiene) diol with a polyisocyanate in the presence of a polyurethane catalyst, optionally followed by chain extension with a diphenol and endcapping with a phenol, oxime, or molecule of formula I:

[0058] [ka]

[0059] (In the formula, R 1 and R 2 is independently selected from hydrogen and C1-C6 alkyl, n is an integer from 1 to 2, and R 3 is a C1-C6 alkyl and is present in an amount of 2-10% by weight, more preferably 3-8% by weight, and particularly preferably 4-6% by weight, based on the total weight of the A moiety).

[0060] Reactive Silanes (a3) Component A comprises at least one reactive silane.

[0061] The reactive silane is any silane that contains a mercapto group, a primary or secondary amine group, or a hydrolyzable silylalkoxy group covalently bonded to an epoxy group.

[0062] In a preferred embodiment, the reactive silane is a mercaptosilane.Preferably, the mercaptosilane is selected from mercaptoalkyl(trialkoxy)silane and mercaptoalkyl(methyldialkoxy)silane.Examples of suitable mercaptosilane include γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyl(methyl-dimethoxy)silane, with γ-mercaptopropyltrimethoxysilane being particularly preferred.

[0063] In another preferred embodiment, the reactive silane is an aminosilane.Preferably, the aminosilane is selected from aminoalkyl(trialkoxy)silane and aminoalkyl(methyldialkoxy)silane.Examples of suitable aminosilane include bis-(trimethoxysilylpropyl)amine, (3-aminopropyl)trimethoxysilane, (3-aminopropyl)triethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, trimethoxysilylpropyldiethylenetriamine, and bis-(trimethoxysilylpropyl)amine, (3-aminopropyl)trimethoxysilane are particularly preferred.

[0064] In another preferred embodiment, the reactive silane is an epoxy silane.Preferably, the epoxy silane is selected from glycidyloxyalkyl(trialkoxy)silane and glycidyloxyalkyl(methyldialkoxy)silane.Examples of suitable epoxy silane include tris(diethylene glycol methyl ether)silyl propylene glycidyl ether, (3-glycidyloxypropyl)trimethoxysilane, (3-glycidyloxypropyl)triethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, and tris(diethylene glycol methyl ether)silyl propylene glycidyl ether is particularly preferred.

[0065] The reactive silane is preferably present in Component A at 0.25 to 2.25 wt. %, more preferably 0.5 to 1.75 wt. %, and especially preferably 0.75 to 1.5 wt. %, based on the total weight of Component A.

[0066] In a preferred embodiment, the reactive silane is selected from glycidyloxyalkyl(trialkoxy)silanes and glycidyloxyalkyl(methyldialkoxy)silanes and is present in an amount of 0.25 to 2.25 wt. %, more preferably 0.5 to 1.75 wt. %, and especially preferably 0.75 to 1.5 wt. %, based on the total weight of component A.

[0067] In a preferred embodiment, the reactive silane is tris(diethylene glycol methyl ether)silyl propylene glycidyl ether and is present at 0.25 to 2.25 wt. %, more preferably 0.5 to 1.75 wt. %, and especially preferably 0.75 to 1.5 wt. %, based on the total weight of component A.

[0068] Thermally conductive filler (a4, b3) The thermally conductive filler used as a4 and b3 is not particularly limited. Suitable thermally conductive fillers have a thermal conductivity of more than 5 W / m°K, more than 10 W / m°K, or more than 15 W / m°K. Examples of thermally conductive fillers include alumina, alumina trihydrate or aluminum trihydroxide, silicon carbide, boron nitride, diamond, and graphite, or mixtures thereof. Particularly preferred embodiments are aluminum trihydroxide (ATH) and aluminum oxide, with ATH being most preferred.

[0069] In a preferred embodiment, the thermally conductive filler has a broad particle size distribution characterized by a D90 / D50 ratio of about 3 or greater. Particularly preferred, the thermally conductive filler is ATH or aluminum oxide, most preferably ATH, having a broad particle size distribution characterized by a D90 / D50 ratio of about 3 or greater.

[0070] Similarly, thermally conductive fillers having a bimodal particle size distribution are also preferred. 90 / D 50 The ratio is about 3 or more, more preferably about 5 or more, and even more preferably about 9 or more. For example, D of 5 to 20 microns 50 and D of 70 to 90 microns 90, especially D of 7 to 9 microns 50 and D of 78 to 82 microns 90 The particle size can be determined using laser diffraction. For ATH, a suitable solvent is deionized water with a dispersing aid such as Na4P2O7x10H2O, preferably at 1 g / l. Preferred are aluminum oxide and ATH, especially ATH, with a bimodal distribution.

[0071] The thermally conductive filler is present in the final adhesive at a concentration of 65-85% by weight, based on the total weight of the adhesive. Preferably, it is present in the final adhesive at a concentration that provides a thermal conductivity of about 1.1 W / mK or greater.

[0072] The thermally conductive filler is present in both the A portion (a4) and the B portion (b3), and the ratio of [a4]:[b3] is 0.7 to 0.9. In a preferred embodiment, the ratio of [a4]:[b3] is 0.72 to 0.87, 0.7 to 0.8, and more preferably 0.73 to 0.87.

[0073] In a preferred embodiment, the thermally conductive filler is used in part (A) at a concentration of 50-80% by weight, more preferably 55-65% by weight, based on the total weight of part A.

[0074] In another preferred embodiment, the thermally conductive filler is used in part (B) at 70-90 wt %, more preferably 75-85 wt %, based on the total weight of part (B).

[0075] In another preferred embodiment, the thermally conductive filler is ATH and is used in part (A) at a concentration of 50-80% by weight, more preferably 55-65% by weight, based on the total weight of part A.

[0076] In another preferred embodiment, the thermally conductive filler is ATH and is used in part (B) at 70-90 wt %, more preferably 75-85 wt %, based on the total weight of part (B).

[0077] In a preferred embodiment, the thermally conductive filler is used in part (A) at a concentration of 50-80 wt.%, more preferably 55-65 wt.%, based on the total weight of part (A), and in part (B) at a concentration of 70-90 wt.%, more preferably 75-85 wt.%, based on the total weight of part (B). In a particularly preferred embodiment, the thermally conductive filler is used in part A at 60 wt.%, based on the total weight of part A, and in part B at 80 wt.%, based on the total weight of part B.

[0078] In a particularly preferred embodiment, the thermally conductive filler is D 90 / D 50 ATH with a ratio of about 8 or greater is used in part (A) at a concentration of 50-80% by weight, more preferably 55-65% by weight, based on the total weight of part A.

[0079] In another preferred embodiment, the thermally conductive filler is D 90 / D 50 ATH with a ratio of about 8 or greater is used in part (B) at 70-90% by weight, more preferably 75-85% by weight, based on the total weight of part (B).

[0080] In a particularly preferred embodiment, the thermally conductive filler is D 90 / D 50 ATH with a ratio of about 8 or greater is used in part A at a concentration of 60% by weight based on the total weight of part A and in part B at a concentration of 80% by weight based on the total weight of part B.

[0081] In a particularly preferred embodiment, the thermally conductive filler is D 90 / D 50 ATH having a ratio of 8 or more, and used in part (A) at 50-80 wt %, more preferably 55-65 wt %, based on the total weight of part (A), and in part (B) at 70-90 wt %, more preferably 75-85 wt %, based on the total weight of part (B). 90 / D 50ATH with a ratio of about 8 or greater is used in part A at 60% by weight based on the total weight of part A and in part B at 80% by weight based on the total weight of part B.

[0082] Other ingredients for component A Component A may include additional optional ingredients such as:

[0083] Additional impact modifiers, such as: Rubber modifiers such as adducts formed from the reaction of epoxy resins with carboxy-terminated butadiene acrylonitrile rubber, preferably 0 to 30% by weight based on the total weight of part A Silicone toughening agent, preferably 0 to 30% by weight based on the total weight of part A Core-shell rubber toughener, preferably 0 to 30% by weight based on the total weight of part A

[0084] Phosphoric acid modified epoxy resin, preferably 0-15% by weight based on the total weight of part A. One or more silane-based adhesion promoters, such as tris(diethylene glycol methyl ether) silyl propylene glycidyl ether.

[0085] Monofunctional, difunctional, and trifunctional epoxy reactive diluents, such as diphenols, monophenols, such as cardanol, C 12~14 -monoglycidyl ethers of alcohols, (trimethylolpropane triglycidyl ether) resins, and diglycidyl ether of cyclohexanedimethanol.

[0086] Plasticizers such as phthalates and dialkyl naphthalenes, particularly dialkyl phthalates, for example diisononyl phthalate, and dialkyl naphthalenes such as diisopropyl naphthalene.

[0087] Reinforcing agents and fillers, such as glass (fibers, flakes, microspheres), carbon fibers, graphite, carbon black, wollastonite (especially high aspect ratio wollastonite), calcium carbonate, TiO2, fumed silica, and any mixtures thereof. The reinforcing agents and / or fillers are preferably used in an amount of 0 to 15% by weight based on the total weight of part A excluding the thermally conductive filler.

[0088] Flame retardants and synergists, such as phosphorus and nitrogen based flame retardants. Examples include melamine polyphosphate, melamine pyrophosphate, melamine cyanurate, aluminum dialkylphosphinates, such as aluminum diethylphosphinate. When used, the flame retardants and synergists are present at 0-10 wt. %, based on the total weight of component A.

[0089] Component B Component B is (b1) at least one polyamine; (b2) at least one catalyst capable of catalyzing the reaction of an amine with an epoxy group; (b3) at least one thermally conductive filler in a concentration of [b3] (wt %) based on the total weight of part B; Includes.

[0090] Each component will be described in turn.

[0091] (b1) at least one polyamine Component B includes at least one polyamine capable of crosslinking with the epoxy groups on the epoxy resin. Polyamines include molecules with two or more amine groups.

[0092] Preferred polyamines include secondary and primary amines, especially polymeric amines, low molecular weight amines, and combinations thereof.

[0093] In a preferred embodiment, the polyamine includes polyetheramine, i.e., a molecule having a polyether backbone with terminal amine groups. Also preferred is the reaction product of a stoichiometric excess of an amine prepolymer with an epoxy resin. The amine prepolymer may be any amine prepolymer having at least two amine groups to allow crosslinking to occur. The amine prepolymer contains primary and / or secondary amine groups, preferably primary amine groups. Suitable amine prepolymers include polyether diamines and polyether triamines and mixtures thereof.

[0094] The polyetheramines may be linear, branched, or mixed. Branched polyetheramines are preferred. Polyetheramines of any molecular weight may be used, with molecular weights in the range of 200 to 6000 or greater being suitable. The molecular weight may be greater than 1000, or more preferably greater than 3000. Molecular weights of 3000 or 5000 are preferred.

[0095] Examples of suitable commercially available polyamines include:

[0096] [Table 1]

[0097] In a preferred embodiment, the polyamine of component B comprises a mixture of TETA and a difunctional primary amine having an average molecular weight of about 2000 and the following general structure:

[0098] [ka]

[0099] (wherein X≈33).

[0100] The concentration of polyamine in Component B depends on the degree of cure desired in the cured adhesive, and also on the desired mix ratio of Components A and B. In a preferred embodiment, the mix ratio (by volume) of Components A to B is 0.8:1 to 1.2:1, especially 1:1, and the NH equivalent per liter of Component B is in the range of 1.5 to 4.50 mol / l, more preferably in the range of 2.50 to 3.75 mol / l, especially preferably 3.00 to 3.40 mol / l.

[0101] In a preferred embodiment, the total amine content in Component B is from 5 to 18% by weight, more preferably from 7 to 15% by weight, and particularly preferably from 9 to 13% by weight, based on the total weight of Component B.

[0102] A catalyst (b2) capable of catalyzing the reaction of an amine with an epoxy group Component B comprises a catalyst capable of catalyzing the reaction of amines with epoxy groups. Suitable catalysts may be Lewis acids or Lewis bases.

[0103] Examples of suitable catalysts are urea and / or tertiary amines, such as p-chlorophenyl-N,N-dimethylurea (monuron), 3-phenyl-1,1-dimethylurea (fenuron), 3,4-dichlorophenyl-N,N-dimethylurea (diuron), N-(3-chloro-4-methylphenyl)-N',N'-dimethylurea 25 (chlortoluron), tert-acryloyl- or alkyleneamines, such as benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, piperidine or derivatives thereof, various aliphatic urea compounds, such as those described in EP 1916272; C1-C 12Alkylene imidazoles or N-arylimidazoles (such as 2-ethyl-2-methylimidazole), or N-butylimidazole and 6-caprolactam, especially 2,4,6-tris(dimethylaminomethyl)phenol incorporated in a poly(p-vinylphenol) matrix (such as described in EP 0197892), or 2,4,6-tris(dimethylaminomethyl)phenol incorporated in a novolac resin (such as described in U.S. Pat. No. 4,701,378) are suitable. Particularly preferred are tertiary amines, especially tris-2,4,6-tris(dimethylaminomethyl)phenol.

[0104] The catalyst is preferably used in an amount of 0.1 to 6% by weight, based on the total weight of component B, more preferably 2 to 5% by weight, particularly preferably 3 or 4% by weight.

[0105] In a preferred embodiment, the epoxy curing catalyst is 2,4,6-tris(dimethylaminomethyl)phenol used at 2-5 wt %, based on the total weight of component B.

[0106] Other ingredients for component B Component B may include additional optional ingredients such as, for example:

[0107] One or more silane adhesion promoters, such as N-(n-butyl)-3-aminopropyltrimethoxysilane.

[0108] Plasticizers such as phthalates and dialkyl naphthalenes, particularly dialkyl phthalates, for example diisononyl phthalate, and dialkyl naphthalenes such as diisopropyl naphthalene.

[0109] Reinforcing agents and fillers, such as glass (fibers, flakes, microspheres), carbon fibers, graphite, carbon black, wollastonite (especially high aspect ratio wollastonite), calcium carbonate, TiO2, fumed silica, and any mixtures thereof. The reinforcing agents and / or fillers are preferably used in an amount of 0-15% by weight, more preferably 0-10% by weight, based on the total weight of part B.

[0110] Curing accelerators, such as p-chlorophenyl-N,N-dimethylurea (monuron), 3-phenyl-1,1-dimethylurea (fenuron), 3,4-dichlorophenyl-N,N-dimethylurea (diuron), N-(3-chloro-4-methylphenyl)-N',N'-dimethylurea 25 (chlortoluron), tert-acryl- or alkyleneamines (such as benzyldimethylamine), 2,4,6-tris(dimethylaminomethyl)phenol, piperidine or its derivatives, various aliphatic urea compounds (such as those described in EP 1916272); C1-C 12 Alkylene imidazoles or N-arylimidazoles (such as 2-ethyl-2-methylimidazole), or N-butylimidazole and 6-caprolactam, especially 2,4,6-tris(dimethylaminomethyl)phenol incorporated in a poly(p-vinylphenol) matrix (such as described in EP 0197892), or 2,4,6-tris(dimethylaminomethyl)phenol incorporated in a novolac resin (such as described in U.S. Pat. No. 4,701,378) are suitable. Particularly preferred are tertiary amines, especially tris-2,4,6-tris(dimethylaminomethyl)phenol. If used, the curing accelerator is preferably present at 0 to 10% by weight, based on the total weight of component B.

[0111] Flame retardants and synergists, such as phosphorus and nitrogen based flame retardants. Examples include melamine polyphosphate, melamine pyrophosphate, melamine cyanurate, aluminum dialkylphosphinates, such as aluminum diethylphosphinate. When used, the flame retardants and synergists are present at 0-10 wt. %, based on the total weight of component B.

[0112] Hardened adhesive In one embodiment, a cured adhesive is provided by mixing components A and B described herein and curing the resulting mixture.

[0113] Components A and B can be mixed by any method that provides a homogenous mixture relatively quickly. In a preferred embodiment, mixing is accomplished using a static mixer as components A and B are dispensed through a nozzle.

[0114] The mixing ratio of component A to component B, A:B, is 0.8:1 to 1.2:1, and more preferably 1:1.

[0115] Adhesive manufacturing method In another aspect, a method for making an adhesive is provided, the method comprising the steps of: (1) preparing an A part resin component, (a1) at least one epoxy resin; (a2) at least one reactive flexibilizer; (a3) at least one reactive silane; (a4) at least one thermally conductive filler having a concentration of [a4] (wt%) based on the total weight of part A a process comprising: (2) preparing a B part hardener component, (b1) at least one polyamine; (b2) at least one catalyst capable of catalyzing the reaction of an amine with an epoxy group; (b3) at least one thermally conductive filler having a concentration of [b3] (wt%) based on the total weight of part B a process comprising: (3) mixing part A and part B in a volume ratio of 0.8:1 to 1.2:1 to form an adhesive mixture such that the concentration of the thermally conductive filler in the adhesive mixture is 65 to 85 weight percent, based on the total weight of the adhesive mixture; A method for producing an adhesive comprising: The ratio of [a4]:[b3] is 0.7 to 0.9. A method for making an adhesive is provided.

[0116] The preferred embodiments of the adhesive described herein apply equally to the method of manufacturing the adhesive.

[0117] The mixing in step (3) can be performed by any method that provides a homogeneous mixture relatively quickly. In a preferred embodiment, the mixing is performed using a static mixer as component B and component B are dispensed through a nozzle.

[0118] In a preferred embodiment, the epoxy equivalents per liter of A part and the NH equivalents per liter of B part are in the range of 0.8:1 to 1.2:1.

[0119] In one embodiment, the volume ratio in step (3) is 1:1.

[0120] In another embodiment, the ratio of [a4]:[b3] is between 0.60 and 0.90.

[0121] In one embodiment of the method, the volume ratio in step (3) is 1:1 and the ratio of [a4]:[b3] is 0.65-0.85.

[0122] In one embodiment of the method, the volume ratio in step (3) is 1:1, the ratio of [a4]:[b3] is 0.65-0.85, and the ratio of epoxy equivalents of part A to NH equivalents of part B is in the range of 0.8:1-1.2:1.

[0123] How to bond two substrates together In another embodiment, there is provided a method for bonding two substrates, comprising the steps of: (1) preparing an A part resin component, (a1) at least one epoxy resin; (a2) at least one reactive flexibilizer; (a3) at least one reactive silane; (a4) at least one thermally conductive filler having a concentration of [a4] (wt%) based on the total weight of part A a process comprising: (2) preparing a B part hardener component, (b1) at least one polyamine; (b2) at least one catalyst capable of catalyzing the reaction of an amine with an epoxy group; (b3) at least one thermally conductive filler having a concentration of [b3] (wt%) based on the total weight of part B A process comprising: (3) mixing part A and part B in a volume ratio of 0.8:1 to 1.2:1 to form an adhesive mixture such that the concentration of the thermally conductive filler in the adhesive mixture is 65 to 85 weight percent, based on the total weight of the adhesive mixture; a process in which the ratio of [a4]:[b3] is 0.7 to 0.9; (4) applying the adhesive mixture to at least one substrate; (5) bringing a second substrate into adhesive contact with the adhesive mixture; and (6) curing the adhesive mixture; A method for bonding two substrates is provided, comprising:

[0124] The preferred embodiments described herein for the adhesive apply equally to the method of adhering substrates.

[0125] The adhesives are particularly suitable for bonding metal to metal, in particular steel, aluminium, magnesium, titanium, nickel plated steel, stainless steel, coated steels commonly used in the automotive industry, e.g. zinc coated steel, zinc magnesium coated steel, metal surfaces coated with organic coatings, e.g. epoxy powder coatings, PET foil, plastic surfaces.

[0126] In a preferred embodiment, the first and second substrates are both metal, in particular steel or aluminium.

[0127] Curing is effected by simply leaving the mixture, preferably at room temperature. Functionally useful cure is typically achieved after 7 days at room temperature. Acceleration of the cure can be achieved by heat. Functionally useful cure can also be achieved after 2 hours at 60°C.

[0128] Efficacy of the disclosed adhesive The cured (7 days, RT) adhesive preferably has a thermal conductivity of 1.0 W / Km or greater, more preferably 1.1 W / Km or greater, as measured according to ASTM 5470-12 in accordance with the examples described herein.

[0129] The cured (7 days, RT) adhesive preferably has an E-modulus of 1,00 MPa or more, more preferably 1000 MPa or more, particularly preferably 4,000 MPa or more, measured according to DIN ISO EN-527-1:2012-06 as described in the examples herein.

[0130] The cured (7 days, RT) adhesive preferably has a lap shear strength of 12 MPa or greater when measured on DX56Z 0.7 mm steel as described in the Examples herein.

[0131] The cured (7 days, RT) adhesive preferably has a T-peel strength of greater than or equal to 1.1 N / mm at 23° C. when measured on DX56Z 0.7 mm steel according to ISO11339:2010.

[0132] The cured (7 days, RT) adhesive preferably has a T-peel failure mode at 23°C of at least 80% cohesive failure, more preferably at least 90% cohesive failure, and especially preferably at least 95% cohesive failure, when measured on DX56Z 0.7 mm steel as described in the Examples herein.

[0133] The cured (7 days, RT) adhesive preferably has a volume resistivity of at least 10 Ω-m, measured as described in the Examples herein.

[0134] In particularly preferred embodiments, the cured (7 days, RT) adhesive has a thermal conductivity of 1.0 W / Km or more, more preferably 1.1 W / km or more, when measured according to ASTM 5470-12 according to the examples described herein, an E-modulus of 100 MPa or more, more preferably 1000 MPa or more, especially preferably 4,000 MPa or more, when measured according to DIN ISO EN-527-1:2012-06 as described in the examples described herein, a lap shear strength of 12 MPa or more, when measured on DX56Z 0.7 mm steel as described in the examples described herein, a T-peel strength of 1.1 N / mm or more at 23° C. when measured on DX56Z 0.7 mm steel according to ISO 11339:2010, and a lap shear strength of 12 MPa or more, when measured on DX56Z 0.7 mm steel as described in the examples described herein. It has a T-peel failure mode at 23°C of at least 80% cohesive failure, more preferably at least 90% cohesive failure, and especially preferably at least 95% cohesive failure, when measured on 0.7 mm steel, and a volume resistivity of at least 10 Ω-m, when measured as described in the Examples herein.

[0135] Purpose The adhesive is particularly suitable for bonding components of battery assemblies in electric vehicles, where thermal conductivity and good structural properties are required, such as bonding battery cells to module or cooling plates, bonding battery modules to cooling plates, etc.

[0136] Specific embodiment examples 1. A two-component thermally conductive adhesive comprising: (A) A portion resin component, (a1) at least one epoxy resin; (a2) at least one reactive flexibilizer; (a3) at least one reactive silane; (a4) at least one thermally conductive filler having a concentration of [a4] (wt%) based on the total weight of part A A resin component comprising: (B) a B part hardener component, (b1) at least one polyamine; (b2) at least one catalyst capable of catalyzing the reaction of an amine with an epoxy group; (b3) at least one thermally conductive filler having a concentration of [b3] (wt%) based on the total weight of part B A B part hardener component comprising Including, A two-component thermally conductive adhesive, wherein, in use, part A and part B are mixed together in a volume ratio of 0.8:1 to 1.2:1 to form an adhesive mixture, the concentration of thermally conductive filler in the adhesive mixture being 65 to 85 weight percent, based on the total weight of the adhesive mixture, and the ratio of [a4]:[b3] being 0.7 to 0.9. 2. An adhesive produced by mixing parts A and B of embodiment 1 in a volume ratio of 0.8:1 to 1.2:1 to form an adhesive mixture, wherein the concentration of the thermally conductive filler in the adhesive mixture is 65 to 85 weight percent, based on the total weight of the adhesive mixture, and the ratio of [a4]:[b3] is 0.7 to 0.9. 3. A method for producing an adhesive, comprising: (1) preparing an A part resin component, (a1) at least one epoxy resin; (a2) at least one reactive flexibilizer; (a3) at least one reactive silane; (a4) at least one thermally conductive filler having a concentration of [a4] (wt%) based on the total weight of part A A process comprising: (2) preparing a B part hardener component, (b1) at least one polyamine; (b2) at least one catalyst capable of catalyzing the reaction of an amine with an epoxy group; (b3) at least one thermally conductive filler having a concentration of [b3] (wt%) based on the total weight of part B a process comprising: (3) mixing part A and part B in a volume ratio of 0.8:1 to 1.2:1 to form an adhesive mixture such that the concentration of the thermally conductive filler in the adhesive mixture is 65 to 85 weight percent, based on the total weight of the adhesive mixture; A method for producing an adhesive comprising: The ratio of [a4]:[b3] is 0.7 to 0.9. How adhesives are manufactured. 4. A method for bonding two substrates comprising the steps of: (1) preparing an A part resin component, (a1) at least one epoxy resin; (a2) at least one reactive flexibilizer; (a3) at least one reactive silane; (a4) at least one thermally conductive filler having a concentration of [a4] (wt%) based on the total weight of part A a process comprising: (2) preparing a B part hardener component, (b1) at least one polyamine; (b2) at least one catalyst capable of catalyzing the reaction of an amine with an epoxy group; (b3) at least one thermally conductive filler having a concentration of [b3] (wt%) based on the total weight of part B a process comprising: (3) mixing part A and part B in a volume ratio of 0.8:1 to 1.2:1 to form an adhesive mixture such that the concentration of the thermally conductive filler in the adhesive mixture is 65 to 85 weight percent, based on the total weight of the adhesive mixture; a process in which the ratio of [a4]:[b3] is 0.7 to 0.9; (4) applying the adhesive mixture to at least one substrate; (5) bringing a second substrate into adhesive contact with the adhesive mixture; and (6) Curing the adhesive mixture A method for bonding two substrates, comprising: 5. Embodiment 1, 2, or 3, wherein the reactive flexibilizer is a polyurethane-based flexibilizer. 6. Any one of the preceding embodiments, wherein the reactive silane comprises a hydrolyzable silylalkoxy group covalently bonded to a mercapto group, a primary or secondary amine group, or an epoxy group. 7. Any one of the preceding embodiments, wherein the reactive silane comprises a mercaptosilane. 8. Embodiment 7, wherein the mercaptosilane is selected from mercaptoalkyl(trialkoxy)silanes and mercaptoalkyl(methyldialkoxy)silanes. 9. Embodiment 7, wherein the mercaptosilane is selected from γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyl(methyldimethoxy)silane. 10. Any one of the preceding embodiments, wherein the reactive silane comprises an aminosilane. 11. Embodiment 10, wherein the aminosilane is selected from aminoalkyl(trialkoxy)silanes and aminoalkyl(methyldialkoxy)silanes. 12. Embodiment 10, wherein the aminosilane is selected from bis-(trimethoxysilylpropyl)amine, (3-aminopropyl)trimethoxysilane, (3-aminopropyl)triethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, trimethoxysilylpropyldiethylenetriamine, in particular bis(trimethoxysilylpropyl)amine. 13. Embodiment 10, wherein the aminosilane is (3-aminopropyl)trimethoxysilane. 14. Any one of the preceding embodiments, wherein the reactive silane comprises an epoxy silane. 15. Embodiment 14, wherein the epoxy silane is selected from glycidyloxyalkyl(trialkoxy)silanes and glycidyloxyalkyl(methyldialkoxy)silanes. 16. Embodiment 14, wherein the epoxy silane is selected from tris(diethylene glycol methyl ether)silyl propylene glycidyl ether, (3-glycidyloxypropyl)trimethoxysilane, (3-glycidyloxypropyl)triethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane. 17. Embodiment 14, wherein the epoxy silane is tris(diethylene glycol methyl ether)silyl propylene glycidyl ether. 18. Any one of the preceding embodiments, wherein the volume ratio of the mixture is 1:1. 19. Any one of the preceding embodiments, wherein the ratio of [a4]:[b3] is 0.72 to 0.87. 20. Any one of the preceding embodiments, wherein the ratio of [a4]:[b3] is 0.72 to 0.8. 21. Any one of the preceding embodiments, wherein the ratio of [a4]:[b3] is 0.75. 22. Any one of the preceding embodiments, wherein the epoxy equivalent weight per liter of A part is 1.50 to 4.50 mol / l. 23. Any one of the preceding embodiments, wherein the epoxy equivalent weight per liter of A part is 2.50 to 3.50 mol / l. 24. Any one of the preceding embodiments, wherein the epoxy equivalents per liter of A part is 3.00-3.30 mmol / l. 25. Any one of the preceding embodiments, wherein the NH equivalents per liter of B component range from 1.50 to 4.50 mol / l. 26. Any one of the preceding embodiments, wherein the NH equivalents per liter of B component range from 2.50 to 3.75 mol / l. 27. Any one of the preceding embodiments, wherein the NH equivalents per liter of component B range from 3.00 to 3.40 mol / l. 28. Any one of the preceding embodiments, wherein the epoxy equivalent weight of the A moiety and the NH equivalent weight of the B moiety are in the range of 0.8:1 to 1.2:1. 29. Any one of the preceding embodiments, wherein the thermally conductive filler is used at a concentration of 50-80% by weight, based on the total weight of part A. 30. Any one of the preceding embodiments, wherein the thermally conductive filler is used in part (A) at a concentration of 55-65% by weight, based on the total weight of part A. 31. Any one of the preceding embodiments, wherein the thermally conductive filler is used in part (B) at a concentration of 70-90% by weight, based on the total weight of part (B). 32. Any one of the preceding embodiments, wherein the thermally conductive filler is used in (B) part at 75-85 wt.%, based on the total weight of (B) part. 33. Any one of the preceding embodiments, wherein the thermally conductive filler is used in the (A) part at a concentration of 55-65 wt %, based on the total weight of the A part, and in the (B) part at a concentration of 75-85 wt %, based on the total weight of the (B) part. 34. Any one of the preceding embodiments, wherein the thermally conductive filler is aluminum trihydroxide. 35. Any one of the preceding embodiments, wherein the thermally conductive filler is ATH having a D90 / D50 ratio of about 8 or greater. 36. Any one of the preceding embodiments, wherein the at least one epoxy resin (a1) is based on bisphenol A, bisphenol F. 37. At least one epoxy resin (a1) has the general formula:

[0137] [ka]

[0138] (wherein n ranges from 0 to about 25). Any one of the preceding embodiments, comprising: 38. Any one of the preceding embodiments, wherein the at least one epoxy resin (a1) has an epoxy equivalent weight in the range of about 155 to 195 g / mol. 39. Any one of the preceding embodiments, wherein the at least one epoxy resin (a1) is a liquid reaction product of epichlorohydrin and bisphenol A, e.g., DER 331, having an epoxide equivalent weight (measured according to ASTM D-1652) of 182 to 192 g / eq, an epoxide percentage (measured according to ASTM D-1652) of 22.4 to 23.6%, an epoxide group content (measured according to ASTM D-1652) of 5200 to 5500 mmol / kg, and a viscosity at 25° C. (measured according to ASTM D-445) of 4000 to 14000 mPas. 40. Any one of the preceding embodiments, wherein the at least one epoxy resin (a1) is a solid epoxy resin that is a low molecular weight solid reaction product of epichlorohydrin and bisphenol A, e.g., DER671, having an epoxide equivalent weight (measured according to ASTM D-1652) of 475 to 550 g / eq, an epoxide percentage (measured according to ASTM D-1652) of 7.8 to 9.1%, an epoxide group content (measured according to ASTM D-1652) of 1820 to 2110 mmol / kg, and a melt viscosity at 150° C. (measured according to ASTM D-4287) of 400 to 950 mPas. 41. Any one of the preceding embodiments, wherein the at least one epoxy resin (a1) is present at 20-40 wt.%, more preferably 25-35 wt.%, and especially preferably 25-30 wt.%, based on the total weight of the A part of the adhesive. 42. Any one of the preceding embodiments, wherein the epoxy resin (a1) is Epoxy 1 and is used at 26-29 wt.%, based on the total weight of Part A of the adhesive. 43. Any one of the preceding embodiments, wherein the reactive flexibilizer (a2) is prepared by reacting at least one polyol and optional poly(butadiene) diol with a polyisocyanate in the presence of a polyurethane catalyst, optionally followed by chain extension with a diphenol and end-capping with a phenol, an oxime, or a molecule of formula I:

[0139] [ka]

[0140] (In the formula, R 1 and R 2 is independently selected from hydrogen and C1-C6 alkyl, n is an integer from 1 to 2, and R 3 is C1-C6 alkyl). 44. Embodiment 43, wherein endcapping is carried out with phenol. 45. Embodiment 43 or 44, wherein the endcapping is carried out with O,O'-diallyl bisphenol A or cardanol. 46. ​​Any one of embodiments 43-45, wherein at least one polyol is a poly(alkylene oxide) diol. 47. Embodiment 46, wherein the poly(alkylene oxide) diol is selected from poly(C2-C6 alkylene oxide) diols, in particular poly(tetramethylene oxide) diol ("PTMEG"), poly(trimethylene oxide) diol ("PO3G"), and mixtures thereof. 48. Any one of embodiments 43-47, wherein the polyisocyanate is selected from toluene diisocyanate, 1,6-hexamethylene diisocyanate ("HMDI" or "HDI"), methylene diphenyl diisocyanate ("MDI"), 2,2,4-trimethylhexamethylene diisocyanate (TMDI), and isophorone diisocyanate (IPDI). 49. Any one of embodiments 43 to 48, wherein the reactive flexibilizer (a2) comprises toluene diisocyanate as the polyisocyanate, poly(propylene oxide) diol or poly(tetramethylene oxide) diol ("PTMEG") as the polyol [which is believed to represent DESMODUR E15], and cardanol as the end-capping group. 50. Any one of embodiments 43 to 48, wherein the reactive flexibilizer (a2) comprises hexamethylene diisocyanate as the polyisocyanate, poly(tetramethylene oxide) diol as the polyol, and O,O'-diallyl bisphenol A as the chain extender and end-capping group. 51. Any one of the preceding embodiments, wherein at least one polyamine (b1) has two or more primary and / or secondary amine functional groups. 52. Any one of the preceding embodiments, wherein the at least one polyamine (b1) is a polyetheramine. 53. Any one of the preceding embodiments, wherein the at least one polyamine (b1) is a di- or tri-amine having a molecular weight of 200 to 6,000 Da. 54. Any one of the preceding embodiments, wherein the at least one polyamine (b1) is a di- or tri-amine having a molecular weight of 1,000 to 2,000 Da. 55. Any one of the preceding embodiments, wherein the at least one polyamine (b1) is selected from:

[0141] [Table 2]

[0142] 56. Any one of the preceding embodiments, wherein the at least one polyamine (b1) comprises a mixture of TETA and a difunctional primary amine having an average molecular weight of about 2000 of the following general structure:

[0143] [ka]

[0144] (wherein X≈33). 57. Any one of the preceding embodiments, wherein the NH equivalents per liter of B moiety range from 1.5 to 4.50 mol / l. 58. Any one of the preceding embodiments, wherein the NH equivalents per liter of B moiety range from 2.50 to 3.75 mol / l. 59. Any one of the preceding embodiments, wherein the NH equivalents per liter of B moiety range from 3.00 to 3.40 mol / l. 60. Any one of the preceding embodiments, wherein catalyst (b2) is selected from urea, tertiary amines, and mixtures thereof. 61. The catalyst (b2) is p-chlorophenyl-N,N-dimethylurea (monuron), 3-phenyl-1,1-dimethylurea (fenuron), 3,4-dichlorophenyl-N,N-dimethylurea (diuron), N-(3-chloro-4-methylphenyl)-N',N'-dimethylurea 25 (chlortoluron), tert-acryl- or alkyleneamines (such as benzyldimethylamine), 2,4,6-tris(dimethylaminomethyl)phenol, piperidine or its derivatives, various aliphatic urea compounds (such as those described in European Patent No. 1916272); C1-C 12 Any one of the preceding embodiments, wherein the alkylene imidazole or N-arylimidazole (such as 2-ethyl-2-methylimidazole), or N-butylimidazole and 6-caprolactam, in particular 2,4,6-tris(dimethylaminomethyl)phenol incorporated in a poly(p-vinylphenol) matrix (such as described in EP 0197892), or 2,4,6-tris(dimethylaminomethyl)phenol incorporated in a novolac resin (such as described in U.S. Pat. No. 4,701,378). 62. Any one of the preceding embodiments, wherein catalyst (b2) is tris-2,4,6-tris(dimethylaminomethyl)phenol. 63. Any one of the preceding embodiments, wherein catalyst (b2) is used at 1 to 6 wt.%, based on the total weight of component B. 64. Any one of the preceding embodiments, wherein catalyst (b2) is used at 2 to 5 wt. %, based on the total weight of component B. 65. Any one of the preceding embodiments, wherein catalyst (b2) is used at 3 or 4 wt.%, based on the total weight of component B. EXAMPLES

[0145] [Table 3]

[0146] [Table 4]

[0147] DER™ 331™ liquid epoxy resin is the liquid reaction product of epichlorohydrin and bisphenol A having an epoxide equivalent weight (measured in accordance with ASTM D-1652) of 182-192 g / eq, an epoxide percentage (measured in accordance with ASTM D-1652) of 22.4-23.6%, an epoxide group content (measured in accordance with ASTM D-1652) of 5200-5500 mmol / kg, and a viscosity at 25° C. (measured in accordance with ASTM D-445) of 11000-14000 mPas.

[0148] Manufacturing of toughening agent GF200 GF200 was produced from the raw materials in Table 2.

[0149] GF200 is the reaction product of Desmodur E15 and Cardolite NX-2026. Reaction procedure: Cardolite NX-2026 and Desmodur E15 are heated to 60°C in a reactor. DABCO T-12N (catalyst) is then added. The reaction mixture is stirred at 80°C for 45 minutes under nitrogen atmosphere, then stirred under vacuum for 10 minutes. The colorless reaction product is then cooled to room temperature and transferred to a container.

[0150] [Table 5]

[0151] Epoxy Adhesive Formulation The raw materials of component A (epoxy resin component) of the comparative examples and the examples of the present invention are shown in Table 3. The raw materials listed in Table 3 are mixed in a planetary mixer or a double asymmetric centrifuge to knead the raw materials. In the first stage, the liquid phase is mixed and then the solid materials are added to the formulation. The formulation is mixed under vacuum for about 30 minutes and then filled into cartridges, pails, or drums.

[0152] The ingredients of component B (amine or hardener component) for the comparative examples and the inventive examples are shown in Table 4. The ingredients listed in Table 4 are mixed in a planetary mixer or a double asymmetric centrifuge to knead the ingredients. In the first stage, the liquid phase is mixed and then the solid materials are added to the formulation. The formulation is mixed under vacuum for about 30 minutes and then filled into cartridges, pails, or drums.

[0153] [Table 6]

[0154] [Table 7]

[0155] The epoxy resin components are summarized in Table 3. Comparative resins 1 and 2 contain 70% by weight of thermally conductive filler and only about 18% epoxy resin. Inventive resins 3 and 4 contain only 60% by weight of thermally conductive filler.

[0156] Comparative Resin 1 and Inventive Resin 3 use the same toughening agent (RAM965), and Comparative Resin 2 and Inventive Resin 4 use the same toughening agent (GF200).

[0157] Table 4 shows the amine hardener components used to cure the different adhesives. Comparative Amine Hardener 1 is designed in a 1:1 mix ratio with a thermally conductive filler level evenly distributed in the resin and hardener components. The filler level is 70% thermally conductive filler by weight. It was used in combination with Comparative Resin 1 and Comparative Resin 2.

[0158] Inventive amine hardener 2 is designed with a higher filler content (80 wt % thermally conductive filler) than the corresponding resin component in a 1:1 mix ratio and was used to mix with inventive resins 3 and 4.

[0159] The amine functionality of the two amine hardener components is tailored to match the epoxy functionality of the epoxy resin component.

[0160] Test Method Rheology Viscosity was measured using a Bohlin rheometer, C / P20, rise / fall 0.1-20s-1 and evaluated according to the Casson model.

[0161] Lap shear strength The lap shear strength was determined according to DIN EN1465:2009 on DX56Z 0.7 mm thick degreased with heptane or on the substrates listed in the table: The bond area is 10×25mm, and the thickness of the adhesive layer is 0.2mm. The failure modes after the lap shear test are analyzed and classified into cohesive failure (CF) and adhesive failure (AF). The values ​​are rounded to the nearest multiple of 10%.

[0162] Tensile Test Plates of the cured adhesive were prepared with a thickness of 2 mm and cured at room temperature for 7 days. Dog-bone shaped test specimens were cut out of the plates. The dimensions were in accordance with DIN ISO EN-527-1 and the tests were carried out on a Zwick tensile testing machine.

[0163] T-peel strength The T-peel strength was measured according to ISO 11339:2010. The samples were DC04ZE (steel) from Thyssen Krupp with a thickness of 0.7 mm. Glass beads with a thickness of 0.2 mm were used as spacers between both strips to adjust the adhesive layer to 0.2 mm. Metal clips were used to hold the two strips together during a 7-day curing cycle at room temperature. The test was performed according to ISO 11339.

[0164] Thermal Conductivity Thermal conductivity was measured on a ZFW Stuttgart Thermal Interface Materials Tester according to ASTM 5470-12. Testing was performed in Spaltplus mode with a thickness of 1.0 mm. The thermal interface materials described were considered to be Type I (viscous liquid) as described in ASTM 5470-12. The upper contact was heated to approximately 40°C and the lower contact was heated to approximately 10°C, resulting in a sample temperature of approximately 25°C. Components A and B were mixed in a static mixer as they were dispensed from a manual cartridge system, and 1.0 mm thick plaques were made to measure the thermal conductivity after curing.

[0165] Volume resistivity The volume resistivity was measured by applying 500 V for 60 seconds in accordance with ASTM D257, IEC 62631-3-1.

[0166] result The test results are summarized in Table 5. Comparative examples are designated "CE" and examples of the invention are designated "IE".

[0167] [Table 8]

[0168] Inventive Example 3 shows a significant improvement in the T-peel failure mode of the adhesive compared to Comparative Example 1, with a failure mode of 100% cohesive failure versus 100% adhesive failure. The same is also true for Inventive Example 4 compared to Comparative Example 2, which shows a failure mode of 100% cohesive failure versus 80% adhesive failure, respectively.

[0169] In addition, the volume resistivity of the inventive example is an order of magnitude better than the comparative example, suggesting that the inventive approach significantly improves electrical properties.

Claims

1. A two-component thermally conductive adhesive comprising: (A) an A portion resin component, (a1) at least one epoxy resin; (a2) at least one reactive flexibilizer; (a3) at least one reactive silane; (a4) at least one thermally conductive filler in a concentration of [a4] (wt %) based on the total weight of part A; A resin component comprising (B) a B part curing agent component, (b1) at least one polyamine; (b2) at least one catalyst capable of catalyzing the reaction of an amine with an epoxy group; (b3) at least one thermally conductive filler having a concentration of [b3] (wt %) based on the total weight of part B; A B part curing agent component comprising Including, A two-component thermally conductive adhesive, wherein in use, part A and part B are mixed together in a volume ratio of 0.8:1 to 1.2:1 to form an adhesive mixture, the concentration of thermally conductive filler in said adhesive mixture being 65 to 85 wt %, based on the total weight of the adhesive mixture, and the ratio of [a4]:[b3] is 0.7 to 0.

9.

2. The adhesive of claim 1 , wherein the reactive flexibilizer is a polyurethane-based flexibilizer.

3. 10. The adhesive of claim 1, wherein the reactive silane comprises a hydrolyzable silylalkoxy group covalently bonded to a mercapto group, a primary or secondary amine group, or an epoxy group.

4. The adhesive of claim 1 , wherein the reactive silane comprises a mercaptosilane.

5. The adhesive of claim 4, wherein the mercaptosilane is selected from mercaptoalkyl(trialkoxy)silanes and mercaptoalkyl(methyldialkoxy)silanes.

6. The adhesive of claim 4, wherein the mercaptosilane is selected from gamma-mercaptopropyltrimethoxysilane and gamma-mercaptopropyl(methyldimethoxy)silane.

7. The adhesive of claim 1 , wherein the reactive silane comprises an aminosilane.

8. The adhesive of claim 7, wherein the aminosilane is selected from aminoalkyl(trialkoxy)silanes and aminoalkyl(methyldialkoxy)silanes.

9. 9. The adhesive of claim 8, wherein the aminosilane is selected from bis-(trimethoxysilylpropyl)amine, (3-aminopropyl)trimethoxysilane, (3-aminopropyl)triethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, trimethoxysilylpropyldiethylenetriamine, and bis-(trimethoxysilylpropyl)amine.

10. The adhesive of claim 9, wherein the aminosilane is (3-aminopropyl)trimethoxysilane.

11. The adhesive of claim 1 , wherein the reactive silane comprises an epoxy silane.

12. 12. The adhesive of claim 11, wherein the epoxy silane is selected from glycidyloxyalkyl(trialkoxy)silanes and glycidyloxyalkyl(methyldialkoxy)silanes.

13. 13. The adhesive of claim 12, wherein the epoxy silane is selected from tris(diethylene glycol methyl ether)silyl propylene glycidyl ether, (3-glycidyloxypropyl)trimethoxysilane, (3-glycidyloxypropyl)triethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane.

14. 14. The adhesive of claim 13, wherein the epoxy silane is tris(diethylene glycol methyl ether)silyl propylene glycidyl ether.

15. 2. The adhesive of claim 1, wherein the volume ratio of the mixture is 1:1.